2018
DOI: 10.12973/iejme/2698
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Teachers’ Subject Matter Knowledge and Pedagogical Content Knowledge in Problem Posing

Abstract: Since the National Council of Teachers of Mathematics ([NCTM], 2000) and the National Research Council ([NRC], 2005) revealed that problem posing needed to be incorporated into mathematics classrooms, the importance of teachers' roles in problem posing has been emphasized in K-12 mathematics curriculum because of instructors' impact on students' mathematical performance. In the present study, researchers investigated teachers' subject matter knowledge (SMK), knowledge of content and teaching (KCT), and knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 22 publications
4
72
0
6
Order By: Relevance
“…It is concluded that transactional leadership style seems to be more reliable choice to create the culture of engagement effectively., it is time for organizations operating in current competitive corporate environment to think beyond then to just motivating their employees and should strive towards creating and encouraging an environment of engagement. It is proved that various types of daily leadership behaviors and styles have a significant and vital direct and indirect influence on subordinates (Lee et al, 2018;Bahremand, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It is concluded that transactional leadership style seems to be more reliable choice to create the culture of engagement effectively., it is time for organizations operating in current competitive corporate environment to think beyond then to just motivating their employees and should strive towards creating and encouraging an environment of engagement. It is proved that various types of daily leadership behaviors and styles have a significant and vital direct and indirect influence on subordinates (Lee et al, 2018;Bahremand, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Asking students to pose a task for a friend is one way to make problem posing meaningful for students (see, for instance, Lowrie 2002). When posing tasks, students can be asked to reformulate or to generate tasks (Lee et al 2018). Both when generating and when reformulating, students can investigate and develop their understanding of mathematical content and ideas, but reformulation requires students to reflect more on the existing problem-solving task (Stickles 2011).…”
Section: Problem Solving and Problem Posingmentioning
confidence: 99%
“…Referring to Burke, benevolence is 'perceived to genuinely care about their subordinates and convey authentic concern in relationships' and can be revealed by concern for others' welfare and helping others. Benevolence characteristics include honesty and cooperative behavior, image (Zawojska 2010), structural and social bonding, empathy, likability, communication effectiveness (Chen, Shi, and Dong 2008), perceived justice and similarity (Lee et al, 2018). The next component is integrity -meaning the trustors' perceived trustee adheres to an acceptable set of principles.…”
Section: Literature Reviewmentioning
confidence: 99%